Association of EPA and DHA with age-related macular degeneration: a cross-sectional study from NHANES - Li, Kewei; Liu, Jialing; Li, Xuhui; Liu, Xiaozhu; Hu, Pengcheng; He, Ming (Frontiers in Medicine, 2024)
Purpose This cross-sectional study conducted in the general U.S. population investigated the association between dietary intake of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and the prevalence of AMD.Methods Data from the National Health and Nutrition Examination Survey (NHANES) were utilized, including 4,842 participants aged 40 years and older. Dietary EPA and DHA intake data were collected through two 24-hour dietary recall interviews and adjusted for weight. AMD was determined by a standardized grading system based on the presence of key features of AMD in color photographs of the macula. Multivariate logistic regression and restricted cubic spline models evaluated the associations between dietary EPA and DHA intake and AMD. Subgroup analysis and interaction analysis explored the influence of covariates.Results A total of 4,842 participants were included. In the multivariate-adjusted model 2, the odds ratios (ORs) with 95% confidence intervals (CIs) for AMD were 0.86 (0.75, 0.99) and 0.88 (0.80, 0.97) per unit increase in dietary EPA and DHA intake, respectively. Interaction testing revealed significant effect modification by age, education, and BMI on the EPA-AMD association, indicating these factors significantly impacted this inverse relationship (p-interaction < 0.05). Similarly, age, education, BMI, and cataract surgery history modified the inverse DHA-AMD association (pinteraction < 0.05). Dose-response analyses demonstrated a negative correlation between dietary EPA and DHA intake with AMD prevalence (p-nonlinearity = 0.184 and 0.548, respectively). Conclusion Our findings suggested that higher dietary EPA and DHA intake could be associated with lower AMD risk in older U.S. adults. Age, education level, BMI, and history of cataract surgery may influence this inverse association.